Echocardiography and cardiorespiratory changes post ketofol or atracurium/ketofol on acepromazine-methadone premedicated dogs - Marwa Abass; Alshimaa Farag; Reham A. Fahmy (Scientific Reports)
Abstract Cardiovascular failure has been recognized as the predominant cause of perioperative mortality in small animals, particularly dogs. This study was designed to evaluate the effectiveness of adding intravenous atracurium to a ketofol infusion during anesthesia in dogs. Thirty male mongrel dogs were premedicated with an intramuscular injection containing 0.02 mg/kg of acepromazine and 0.2 mg/kg of methadone. Thirty minutes later, the dogs were equally and randomly divided into two groups (n = 15): the Ketofol Group (KFG), in which anesthesia was induced using IV administration of 0.5 ml/kg of ketofol, and the atracurium/ketofol Group (AKFG), in which anesthesia was induced using IV administration of 0.25 mg/kg of atracurium with 0.5 ml/kg of ketofol. Following intubation, anesthesia was maintained by a variable intravenous infusion at 0.2 ml/kg/min in KFG or a combination of 0.01 mg/kg/min atracurium and 0.2 ml/kg/min ketofol in AKFG. Respiratory frequency (fR), mean arterial pressure (MAP), heart rate (HR), oxygen saturation of hemoglobin (SpO2), end-tidal carbon dioxide concentration (EtCO2), rectal temperature (RT), the quality of induction, intubation, recovery period, ejection fraction percentage (EF%), fractional shortening percentage (FS%), and stroke volume (SV) were recorded. The ketofol doses were significantly lower, P ≤ 0.01, in the AKFG group (4.2 ± 0.44 mg/kg) than in the KFG group (2.27 ± 0.6 mg/kg). There were statistically significant increases in RR, HR, MAP, EtCO2, and echocardiography parameters in the AKFG group compared to the KFG group. Additionally, the AKFG group exhibited a significant reduction in induction, intubation, and recovery scores compared to the KFG group. Adding atracurium to ketofol during dog anesthesia positively impacts the hemodynamic and cardiac parameters and improves the quality of induction, intubation, and recovery.